PENGEMBANGAN INSTRUMEN TES KETERAMPILAN DRIBBLING PADA PEMAIN SEPAKBOLA USIA 18 SAMPAI 23 TAHUN - FAJAR RAMADHAN, MOCHAMMAD; WIDODO, ACHMAD (Jurnal Kesehatan Olahraga, 2019)
ABSTRACTTechnique dribbling in football is one of the important basic techniques at a certain moment and damaging the opponents defense and bypassing the opponent when attacking the opponents defense, some test instruments of existingskills dribbling , researchers find weaknesses of existing instruments, with the development of game patterns modern football in the present era. So researchers want to develop existing instruments to be updated and make the test instruments valid. The aim of the study was to determine the development of test instruments throughguidelines for dribbling validfootball players or athletes aged 18 years and over. The type of research usedis the development of R & D (Research and Development), usingthe purposive sampling method. The target in this study was 50 Al-Rayyan club player in the city of Surabaya. The research was carried out in East Java Koni Athletic Field and in the Bungurasih Field Surabaya.. The research instrument used in this study was direct interviews, football expert practitioners and developed test instruments in the form of product designs that had been made and applied to soccer players. Results from the study of a series of tests shows the results of the correlation that (X1)TDN with (Y) Small Set is invalid because the game is said to have r -0.225 <r table = 0.396 and has the opposite correlation coefficient value (negative), while the (X2) TDK with (Y) Small Set Game is said to be valid with r value of -0.4471> r table = 0.396 but has an opposite correlation coefficient (negative). The validity test of the Nurhasan dribbling instrument correlated with the coachs assessment through the small side games is invalid because the calculated r value is smaller than the r table, but different from the new product developed by the instrument researcher is valid because it gets the r value above from the r table value but the value obtained is leaning towards a negative value. Keywords: Instrument Development Test, Football, DribblingABSTRAKTeknik dribbling dalam sepakbola merupakan salah satu teknik dasar yang penting pada saat momen tertentu dan merusak pertahanan lawan serta melewati lawan pada saat menyerang pertahanan lawan, beberapa instrument tes keterampilan dribbling yang sudah ada, peneliti menemukan kelemahan dari instrumen yang sudah ada, dengan perkembangan pola permainan sepakbola modern di era sekarang. Maka peniliti ingin mengembangkan instrument yang sudah ada untuk diperbarui dan menjadikan instrument tes tersebut menjadi valid. Tujuan penelitian untuk mengetahui pengembangan instrumen tes melalui petunjuk pelaksanaan dribbling yang valid pada pemain atau atlet sepakbola usia 18 tahun ke atas. Jenis penelitian yang digunakan yaitu pengembangan R&D (Research and Development), menggunakan metode purposive sampling. Sasaran pada penelitian ini adalah 50 pemain sepakbola club Al-Rayyan Kota Surabaya. Penelitian dilaksanakan Lapangan Atletik Koni jawa timur dan di lapangan Bungurasih Surabaya.. Instrumen penelitian yang digunakan pada penelitian ini adalah wawancara langsung, praktisi ahli sepakbola dan mengembangkan instrumen tes yang berupa desain produk yang telah di buat dan di aplikasikan kepada pemain sepak bola. Hasil dari penelitian dari serangkaian tes menunjukan dari hasil korelasi bahwa (X1) TDN dengan (Y) Small Set Game dikatakan tidak valid dikarenakan memiliki r -0,225 < r tabel = 0,396 dan memiliki nilai koefisien korelasi berlawanan (negatif), sedangkan (X2) TDK dengan (Y) Small Set Game dikatakan valid dengan nilai r -0,471 > r tabel = 0,396 namun memiliki nilai koefisien korelasi berlawanan (negatif). uji validitas instrumen dribbling nurhasan yang dikorelasikan dengan penilaian pelatih melalui permainan small side games tidak valid dikarenakan nilai r hitung lebih kecil daripada r tabel,namun berbeda dengan produk baru yang dikembangkan oleh peneliti instrument tersebut valid dikarenakan mendapatkan nilai r hitung yang diatas dari nilai r tabel tetapi nilai yang didapat bercondong kearah nilai negative. Kata kunci : Instrumen Pengembangan Tes, Sepakbola, Dribbling